Appraisal of Fixed Assets of a Public Sector Undertaking: A Case Study of Madhya Pradesh State Agro Industries Development Corporation Limited - Khatik, S. K.; Nag, Amit Kr. (Indian Journal of Finance, 2013)
An appraisal of fixed assets is nothing but a particular process of identifying the points of strength and weaknesses by properly establishing a relationship between fixed assets and some other variables, either in the balance sheet, or in the profit and loss account. Such an analysis can be undertaken by the management of a firm, or any party outside a firm, i.e. owners, creditors, investors, research scholars, etc. Undoubtedly, fixed assets constitute an important place in the capital employed by an enterprise, and they also play an important role towards the successful operation of a firm’s business. But the utility of fixed assets cannot be judged unless an analysis of fixed assets is made with respect to their productivity, efficiency, performance and profitability, irrespective of their share in the capital employed because there may be cases where the fixed assets occupied a major proportion of the total capital employed, while the profitability was very low and vice versa. The present study examines fixed assets for this purpose through important and selected ratios with special reference to Madhya Pradesh State Agro Industries Development Corporation Limited.